The TESS Mission Target Selection Procedure. (8th September 2021) - Fausnaugh, Michael; Morgan, Ed; Vanderspek, Roland; Pepper, Joshua; Burke, Christopher J.; Levine, Alan M.; Rudat, Alexander; Villaseñor, Jesus Noel S.; Vezie, Michael; Goeke, Robert F.; Ricker, George R.; Latham, David W.; et al.
Abstract: We describe the target selection procedure by which stars are selected for 2 minute and 20 s observations by TESS. We first list the technical requirements of the TESS instrument and ground systems processing that limit the total number of target slots. We then describe algorithms used by the TESS Payload Operation Center (POC) to merge candidate targets requested by the various TESS mission elements (the Target Selection Working Group, TESS Asteroseismic Science Consortium, and Guest Investigator office). Lastly, we summarize the properties of the observed TESS targets over the two-year primary TESS mission. We find that the POC target selection algorithm results in 2.1–3.4 times as many observed targets as target slots allocated for each mission element. We also find that the sky distribution of observed targets is different from the sky distributions of candidate targets due to technical constraints that require a relatively even distribution of targets across the TESS fields of view. We caution researchers exploring statistical analyses of TESS planet-host stars that the population of observed targets cannot be characterized by any simple set of criteria applied to the properties of the input Candidate Target Lists.